(Invited) On the Electrical Activity of Extended Defects in High-Mobility Channel Materials. (14th September 2015) - Simoen, Eddy; Eneman, Geert; Hikavyy, Andriy Yakovitch; Loo, Roger; Gupta, Somya; Merckling, Clement; Alian, AliReza; Schulze, Andreas; Caymax, Matty; Langer, Robert; Barla, Kathy; Claeys, Cor
Abstract : The electrical activity of extended defects (dislocations; antiphase boundaries;...) in high-mobility channel materials (strained-Si; (strained)-Ge, GaAs and InGaAs) is investigated by means of simple device structures (p-n diodes and MOS capacitors). These are fabricated in substrates with a well-controlled density of predominant extended defects, enabling the determination of a specific leakage current contribution per defect. It is shown that there is a linear relationship between the area leakage current density and the threading dislocation density for a wide range of group IV p + n junctions. In the case of antiphase boundaries (APBs) of GaAs on Ge substrates, only a moderate electrical activity has been derived from these studies. On the other hand, a clear band of deep states has been demonstrated for TDs in InGaAs layers on GaAs substrates.